Using a State Birth Registry as a Quality Improvement Tool - Lannon, Carole; Kaplan, Heather C.; Friar, Kelly; Fuller, Sandra; Ford, Susan; White, Beth; Besl, John; Paulson, John; Marcotte, Michael; Krew, Michael; Bailit, Jennifer; Iams, Jay (American Journal of Perinatology, 2017)
Background Birth registry data are universally collected, generating large administrative datasets. However, these data are typically not used for quality improvement (QI) initiatives in perinatal medicine because the quality and timeliness of the information is uncertain.Objective We sought to identify and address causes of inaccuracy in recording birth registry information so that birth registry data could support statewide obstetrical quality initiatives in Ohio.Study Design The Ohio Perinatal Quality Collaborative and the Ohio Department of Health Vital Statistics used QI techniques in 15 medium-sized maternity hospitals to identify and remove systemic sources of inaccuracy in birth registry data. The primary outcome was the rate of scheduled deliveries without medical indication between 370/7 and 386/7 weeks at participating hospitals from birth registry data.Results Inaccurate birth registry data most commonly resulted from limited communication between clinical and medical record staff. The rate of scheduled births between 370/7 and 386/7 weeks' gestation without a documented medical indication as recorded in the birth registry declined by 35%.Conclusion A QI initiative aimed at increasing the accuracy of birth registry information demonstrated the utility of these data for surveillance of perinatal outcomes and has led to ongoing efforts to support birth registrars in submitting accurate data.
Keywords: birth registry data; quality improvement; perinatal outcomes; population health